The driving role of extracellular polymeric substances in the bioelectrical conversion of petroleum hydrocarbons by rhizosphere microbial fuel cells: bioelectricity production, substrate bioconversion, microbial function and their network correlation - Lanmei Zhao; Yuru Wen; Lyu Can; Long Meng; Jian Liu; Dong Zhao (Bioresources and Bioprocessing)
Abstract Extracellular polymeric substances (EPS), are crucial components of biofilms that drive the bioelectrical conversion of petroleum hydrocarbons (PHCs), but their role has not been adequately addressed. This research explores the driving role of EPS in bioelectrical PHC conversion by rhizosphere microbial fuel cells (MFCs). We found that current density, output voltage, coulombic efficiency, power density, current stabilization time, metabolite volatile fatty acid (VFA) production and PHC biodegradation ratio initially increased and then decreased with rising initial EPS level (0-128 mg·g− 1), peaking at 64 ± 1 mA·m− 2, 8.04 ± 0.16 V, 60.9 ± 1.2%, 129 ± 3 mW·m− 2, 23 ± 1 days, 1.77 ± 0.04 g·kg− 1 and 66.7 ± 1.5%, respectively. Fluorescence intensity of proteins having tyrosine-tryptophan demonstrated a continuous enhancement, consistent with increased biofilm thickness. Within an appropriate range of initial EPS levels (0–64 mg·g⁻¹), bioelectricity generation and PHC bioconversion enhanced as the EPS content rose in mature biofilms. However, excessive EPS addition could increase biofilm thickness to 0.48 mm, which in turn reduced biofilm activity and overall system performance. The abundances of electrochemically active and PHC-degrading bacteria presented an initial increase followed by a subsequent decrease as the initial EPS level rose, highlighting that EPS at the optimal level enriched and activated these functional bacteria. The positive correlations between the relative abundances of these bacteria and various metrics of bioelectricity generation and PHC bioconversion underscored the critical role of EPS in shaping microbial community structure and enhancing electron transfer efficiency through biofilm formation and stabilization. These findings not only provide a critical theoretical foundation and novel ideas to promote the conversion of PHC into renewable bioenergy but also highlight the potential scalability and environmental benefits of this technology in the field of clean remediation of PHC-polluted soils and recovery of bioenergy. Integrating EPS-driven MFCs with other renewable energy technologies will offer promising opportunities to develop hybrid systems that generate clean energy while mitigating environmental pollution. Furthermore, this approach also has the potential as biosensors for the real-time detection of PHCs, thus contributing to broadening its application in environmental monitoring. Graphical Abstract